Undang-Undang Nasional yang Memadai: Menilai Ketidakperluan Ratifikasi Statuta Roma - Fadilah Septiarahma; R. Aj. Nindya Rizky Utamie; Katharina Stogmuller (CV. ULIL ALBAB CORP, 2024)
The Rome Statute, which is the basis for the establishment of the International Criminal Court, has not been ratified or signed by Indonesia. This makes Indonesia a non-state party to the Rome Statute. The background of the government's refusal to ratify the Rome Statute is a complex reason such as legal, political and social. National laws have been sufficient in dealing with serious crimes such as crimes against humanity and genocide, so the government considers it unnecessary to ratify the Rome Statute.